Trade-Offs in modeled phosphorus acquisition strategies and the marine N2 fixation paradox - Landolfi, Angela; Dietze, Heiner; Oschlies, Andreas (2011)
Marine N2 fixation is known to be energetically expensive and limited by Fe and P. Slow growing N2 fixers should have a competitive advantage only when N limits primary production and thus should out-compete non-fixing phytoplankton in N-limited ecosystems. This paradigm has forged the way N2 fixation is parameterized in global marine biogeochemical models. However, state-of-the-art global coupled circulation- ecosystem models fail to reproduce the paradoxical observations of high N2 fixation rates in N-rich areas like the tropical North Atlantic, implying that our current understanding of oceanic N2 fixation is incomplete. Here, we employ a global coupled ecosystem-circulation model to test diefferent N2 fixation parameterizations and explore a cost-benet approach inherent to the acquisition of dissolved organic phosphorus (DOP). Increasing the degree of realism of N2 fixation representation in biogeochemical ocean models will improve our mechanistic understanding of marine diazotrophy and will advance our ability to predict changes in the oceanic N inventory.